Strategi Perbankan Syariah Dalam Menghadapi Pembiayaan Dengan Akad Mudharabah Yang Bermasalah (Studi di Bri Syariah Pamekasan) - Samsul Arifin (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
Islamic banking has a main function to distribute funds to the community in need in the form of financing. Financing is a large part of the assets of sharia banks that must be maintained in term of quality. Financing is one of the functions of sharia banks by distributing funds to the community in need (user of funds). One of the contracts used by sharia banks in distributing funds in the form of financing is mudharabah contract. The mudharabah contract is a profit-sharing agreement when the shohibul mall /rabbul mall provides capital (100 percent) to mudharib, to engage in productive activities in which the profit generated will be divided among them according to the agreement specified in the contract.This study is aimed to know and understand how the application of mudaraba contracts and banking strategies in overcoming a financing with mudaraba contracts that are problematic, and to know and understand whether the applied strategy is in accordance with the Fatwa (policies) of DSN MUI.The method used in this research is descriptive qualitative research method or naturalistic research because the research is done on natural condition (natural setting). This descriptive qualitative research method is used to get in-depth data, a data that contains meaning.The findings of the research done in BRI Syariah Pamekasan in facing the financing problems with the mudharabah contract, found two problems. First, the problem arising from the internal banking itself, this problem occurs when BRI Syraiah employees do not run the SOP (procedures) that has been set. Second problem is the external factor of banking. This problem occurs because mudharib/ fund manager has moral hazard. For example, by not using the funds for productive business but used for consumptive costs.Efforts done by BRI Syariah Pamekasan dealing with mudharabah financing problem is by using two approaches. First, the pre-customer approach. This approach focuses on selecting prospective customers both in terms of behavior/ character and business run. Second, the post-customer approach. This approach is carried out when the financing has been distributed to customers and experiencing non-performing financing. This is done by monitoring and restructuring Keywords: Financing, mudharabah contract, banking strategy.